A NEW ALLOSTERIC BIS CROWN ETHER LIGAND CONTAINING A 2,2'-BIPYRIDYL FRAGMENT - Beer, P; Rothin, A (1988)
The synthesis of a new allosteric bis crown ether ligand incorporating a 2,2′-bipyridyl function and two benzo-15-crown-5 subunits is described. Chelation of Ru(II) at the bipyridyl nitrogens forces the bipyridyl function towards coplanarity, restricting the conformational freedom of the two benzo-15-crown-5 binding units in such a way as to favour the formation of an intramolecular sandwich complex with sodium. A variety of bimetallic complexes have been isolated resulting from the simultaneous coordination of transition metals at the bipyridyl fragment and alkali metals at the crown ether moieties. © 1988.